2023
DOI: 10.3389/fphar.2023.1233184
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in rat brain during experimental status epilepticus: effect of antioxidants

Marius Fuchs,
Christian Viel,
Alina Lehto
et al.

Abstract: Antioxidants have been proposed as a treatment for diseases of the central nervous system. However, few studies actually studied their effects in the brain. To test central actions of antioxidants, we used the lithium–pilocarpine (Li-Pilo) model of status epilepticus (SE) in the rat in which seizures are accompanied by significant oxidative stress. We used in vivo microdialysis to determine isoprostane levels during SE in real time and brain homogenates for other measures of oxidative stress. Six different ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…To find a potential mechanism for mitigating oxidative stress in severely diseased-iNSCs, we treated the cells with the antioxidant compound AA (vitamin C) prior to the administration of H 2 O 2 . Previous studies have already demonstrated the protective effects of AA in reducing neuronal damage when administered before the induction of seizures in rats 77 , 78 . In our model, pre-treatment of diseased iNSCs with AA in the presence of oxidative stress led to an up-regulation of proteins associated with cellular protection, such as HSPB1 and p62.…”
Section: Discussionmentioning
confidence: 92%
“…To find a potential mechanism for mitigating oxidative stress in severely diseased-iNSCs, we treated the cells with the antioxidant compound AA (vitamin C) prior to the administration of H 2 O 2 . Previous studies have already demonstrated the protective effects of AA in reducing neuronal damage when administered before the induction of seizures in rats 77 , 78 . In our model, pre-treatment of diseased iNSCs with AA in the presence of oxidative stress led to an up-regulation of proteins associated with cellular protection, such as HSPB1 and p62.…”
Section: Discussionmentioning
confidence: 92%
“…The GSH/GSSG ratio, a key antioxidant measure, was not significantly altered in whole brain tissue homogenate in the current study, possibly due to regional variations. Contrasting findings in studies analyzing specific brain regions like the hippocampus or striatum underscore the importance of localized assessments [73][74][75][76][77]. Also, if, in the case of human samples, the level of GSH in the brain can vary pre-and post-mortem, the same can happen in experimental animals [78].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, SE promotes an excessive production of free radicals and reactive oxygen species (ROS), which in turn facilitates the establishment of oxidative stress (OS) and contributes to neurodegeneration and epileptogenesis. 9 , 10 , 11 DM also increases ROS generation by affecting different metabolic pathways including glycolysis, glucose auto‐oxidation, sorbitol pathway, protein glycation, and mitochondrial electron transport chain activity, 12 and decreases the body's endogenous antioxidant response, 13 which generates a redox imbalance and triggers OS. This redox imbalance may contribute to DM‐associated brain complications like seizures.…”
Section: Introductionmentioning
confidence: 99%